Development And Validation Of A Technology Ability Test (TAT) For Admission Of Students Into Technology Teacher Education Programmes In Nigerian Universities - E. Inyiagu, Emmanuel (European Scientific Journal, ESJ, 2016)
This study was an instrumentation research. The purpose of the study was to develop and validate a Technology Ability Test (TAT) for admission of students into Technology Teacher Education Programmes in Nigerian Universities. A sample of 120 students drawn from four universities in the southeast geopolitical zone of Nigeria that offers the programme was used for the study. Six research questions were answered and two hypotheses tested in the study. The 50 – items TAT that emerged after the preliminary testing was used for data collection. Results of TAT’s psychometric qualities indicated that 80 percent of the items possessed moderate difficulty and high (suitable) discrimination indices. The reliability coefficient obtained from the test is 0.96, which indicates that TAT is very reliable. Results further revealed that gender has slight influence on the Technology Ability Test, students of the federal universities performed marginaly better than their state counterparts and that TAT scores has very low concurrent validity with JAMB scores. The educational implications of the findings when the developed Technology Ability Test (TAT) is adopted included helping admission officers and counselors to objectively identify students with the capability to succeed in technology teacher education programmes in Nigerian Universities and data obtained after the administration will provide efficient indices for future performances of students in technology teacher education, since a valid ability test is also predictive. Based on the findings of this study, the researcher recommended that the developed test be used in admiting candidates into technology teacher education programmes and admission officers be trained on how to use the newly developed test.